2011
DOI: 10.1590/s1984-70332011000400005
|View full text |Cite
|
Sign up to set email alerts
|

Preculture sugarcane tissue in sucrose-supplemented culture medium to induce desiccation tolerance

Abstract: Cryopreservation is a promising technique for long term conservation of sugarcane's genetic resources which could be used in breeding programs. Preculture is a key step for success this technique. The purpose of this study was to evaluate the effect of sucrose concentrations and preculture period on dessication tolerance of sugarcane tissue dehydrated to 30, 20 and 10 % moisture. Sugarcane shoot tips were encapsulated in sodium alginate and precultured in a liquid culture medium with 0.3, 0.5, and 0.75 M sucro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…With the V cryoplate method, large sugarcane shoot tips resulted in higher regrowth than smaller ones (Rafique et al, 2015). Melo et al (2011) also found that large explants could accumulate carbohydrate in the form of starch grains that could serve as an energy source for the regeneration of sugarcane shoot tips after cryopreservation. Moreover, Chaireok et al (2016) reported that vigor regrowth could be observed in large postcryopreserved P. niveum calli with high carbohydrate accumulation.…”
Section: Resultsmentioning
confidence: 94%
“…With the V cryoplate method, large sugarcane shoot tips resulted in higher regrowth than smaller ones (Rafique et al, 2015). Melo et al (2011) also found that large explants could accumulate carbohydrate in the form of starch grains that could serve as an energy source for the regeneration of sugarcane shoot tips after cryopreservation. Moreover, Chaireok et al (2016) reported that vigor regrowth could be observed in large postcryopreserved P. niveum calli with high carbohydrate accumulation.…”
Section: Resultsmentioning
confidence: 94%
“…Despite the many advantages of cryopreservation, viable protocols that can guarantee good rates of regeneration of the material after cryopreservation are not yet available for most species, thus limiting its application for long-term germplasm conservation (Funnekotter et al 2017). Several factors can influence plant recovery after immersion in liquid nitrogen, including the age of the mother plant that provided the explant, resistance of tissues during dissection, the type of cryoprotectant solution employed, the time of exposure to it, and the specific cryopreservation techniques to be employed (Sakai and Engelmann 2007, Uchendu and Reed 2008, Melo et al 2011, Engelmann 2014.…”
Section: Introductionmentioning
confidence: 99%
“…Cryopreservation techniques that make use of shoot tips excised from in vitro-grown plants have been published for many genera, including Saccharum. Paulet et al (1993), González-Arnao et al (1999), González-Arnao and Engelmann (2006) and Melo et al (2011) all published encapsulation-dehydration methods that demonstrated successful cryopreservation of sugarcane cultures. These techniques precultured shoot tips on medium supplemented with 0.5 to 0.75 M sucrose prior encapsulation in calcium-alginate beads.…”
Section: Introductionmentioning
confidence: 99%
“…Beads were then dehydrated to moisture contents of 20 to 25%, and then plunged into liquid nitrogen (LN). Regrowth levels were highly variable, ranging from 14 to 91% for S. officinarum cultivars (Paulet et al, 1993;González-Arnao et al, 1999;González-Arnao and Engelmann, 2006;Melo et al, 2011).…”
Section: Introductionmentioning
confidence: 99%